Juridical Review of the Evidentiary Power as the Basis for Determining a Suspect Under Article 184 of the Criminal Procedure Code (Pretrial Decision Number: 33/Pid.Prap/2020/Pn Jkt Sel) - Sulmainingsih Sulmainingsih (Journal of Social Research, 2025)
The determination of suspects is a crucial stage in the investigation process because it has direct implications for a person's human rights. The Criminal Procedure Code expressly requires the existence of sufficient preliminary evidence, namely at least two valid pieces of evidence as stipulated in Article 184 of the Criminal Procedure Code. The Constitutional Court Decision Number 21/PUU-XII/2014 also emphasizes that the determination of suspects must meet these standards. This study aims to analyze the strength of evidence as the basis for determining suspects and examine the judge's considerations in Pretrial Decision Number 33/Pid.Prap/2020/PN. Jkt.Cell which stated that the determination of the suspect was invalid because the minimum requirements for evidence were not met. The research method used is normative legal research with a legislative and conceptual approach. The results of the study show that the valid evidence in Article 184 of the Criminal Code has a fundamental function as a formal and material requirement in the determination of suspects. In the pretrial case, the judge considered that the evidence submitted by the investigators did not meet the adequacy standards, both in terms of quality and quantity, so it could not be used as a basis to designate someone as a suspect. This ruling emphasizes that investigators are obliged to act professionally, transparently, and carefully in the investigation process to prevent repressive actions and human rights violations. This research is expected to make a theoretical contribution to the development of criminal procedural law and become a practical reference for law enforcement officials in applying evidentiary standards in accordance with the Criminal Procedure Code and the principles of the state of law.